Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Keberhasilan Proyek Asa Casa di Kabupaten Gianyar - I Made Yuliana Mahendra; Komang Agus Ariana; I Gusti Ngurah Putu Dharmayasa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The success of construction projects is greatly influenced by human resource factors, particularly employee motivation and job satisfaction. This study aims to analyze the influence of motivation and job satisfaction on the success of the Asa Casa Project in Gianyar Regency, as well as to identify the most dominant factors among the two variables. The research method used is descriptive quantitative, with data collected through questionnaires. A sample of 30 respondents was analyzed using Pearson correlation test with the help of SPSS version 24. The results show that work motivation has a significant influence on project success (r = 0.638; p < 0.01), while job satisfaction does not show a significant influence (r = 0.202; p > 0.05). The most dominant motivational factor is the relationship with coworkers, while for job satisfaction, it is the nature of the job itself. These findings highlight the importance of management’s focus on motivation to improve productivity and project success. This study is expected to serve as a reference for human resource management in similar construction projects.